Regional planning in Ireland - case for concentration - reappraisal - O'Farrell, PN (Economic & Social Studies, 1974)
Few development issues in Ireland have generated so much controversy and emotion as the concept of spatially polarised growth; yet the continuing discussion has often been confused by a notable failure to define terms and concepts clearly and a tendency to recommend radical policy iniatives on the basis of flimsy and often unscientific evidence. It is against this background that Helen O'Neill entered the debate and has advocated that a high degree of spatially concentrated investment should constitute the fundamental basis of Irish regional policy.
Keywords: Regional Planning; Ireland